Multiple caldera collapses inferred from the shallow electrical resistivity signature of the Las Cañadas caldera, Tenerife, Canary Islands - Coppo, Nicolas; Schnegg, Pierre-André; Heise, Wiebke; Falco, Pierik; Costa, Roberto (My University, 2008)
The Las Cañadas caldera of Tenerife (LCC) is a well exposed caldera depression filled with pyroclastic deposits and lava flows from the active Teide–Pico Viejo complex (TPVC). The caldera's origin is controversial as both the formation by huge lateral flank collapse(s) and multiple vertical collapses have been proposed. Although vertical collapses may have facilitated lateral slope failures and thus jointly contribute to the exposed morphology, their joint contribution has not been clearly demonstrated. Using results from 185 audiomagnetotelluric (AMT) soundings carried out between 2004 and 2006 inside the LCC, our study provides consistent geophysical constraints in favour of multiple vertical caldera collapse. One-dimensional modelling reveals a conductive layer at shallow depth (30–1000 m), presumably resulting from hydrothermal alteration and weathering, underlying the infilling resistive top layer. We present the resistivity distribution of both layers (resistivity images), the topography of the conductive layer across the LCC, as well as a cross-section in order to highlight the caldera's evolution, including the distribution of earlier volcanic edifices. The AMT phase anisotropy reveals the structural and radial characteristics of the LCC.
Keywords: audiomagnetotellurics; caldera; hydrothermal alteration; conductive layer; Tenerife